The Pasar Siti Khadijah of Kelantan / Suraya Husin and Siti Maziah Ab Rahman - Husin, Suraya; Ab Rahman, Siti Maziah (Faculty of Art and Design, 2021)
This work shows the situation from one corner of the Siti Khadijah Market, Kota Bharu, Kelantan. The original name of Pasar Besar Siti Khadijah is Pasar Besar Buluh Kubu. However, it was renamed to this name by the ex-Menteri Besar of Kelantan, Allahyarham Tuan Guru Dato 'Nik Abdul Aziz Bin Nik Mat as a sign of respect to the Hawa race, as the majority of its traders are women. This landmark in the heart of Kota Baru in Kelantan is named after Prophet Muhammad’s first wife who was a savvy businesswoman. The name is an apt representation of the bustling market as the majority of businesses here are run by women. This market is octagonal in shape and consists of four levels. A unique sight in the markets in Kelantan is the traders who on average consist of women who are known for their business interests. This market consists of the elements of the Malays, gentleness, politeness and the real identity of the people of Kelantan. Pasar Siti Khadijah – with its cacophony of sights, sounds and scents that are typical of a local market – is definitely the place to be.